Соціалізація економіки як нова парадигма економічної теорії - Попадинець, Олена Василівна (Українська державна академія залізничного транспорту, 2015)
Стаття присвячена причинам необхідності оновлення парадигми економічної теорії на сучасному етапі в умовах глобальної соціально-економічної кризи. Саме соціальний вектор у розвитку суспільства та його домінування у економічних відносинах має дозволити узгодити інтереси різних верств населення, подолати існуючу майнову нерівність, забезпечити зростання добробуту та соціального благополуччя.

The article outlines the necessity of redefining the economic theory’s paradigm under the circumstances of current global socio-economic crisis. Consumer Society Theory based on the approaches of neoclassic mainstream has proven its deficiency. That prompts the development of new paradigm in economic theory. The interests of different social layers in the society should be consolidated according to social vector. Socialization of economy could alleviate the problem of economic inequality, enhance social and economic welfare. It could help to manage socio-labor relationship in a more efficient way, lessen social risks and frequency of conflicts; reduce income gaps. It would also increase motivation of labor force and competitiveness of the economy in general. Socialization of economy would help to make well-being of people and their personal development as a main target of production activity.
Socialization of economy as a new paradigm in economic theory
Keywords: соціалізація; гуманізація; майнова диференціація; бідність; криза індустріалізму; socialization; humanization; income inequality; poverty; crisis of industrialisms; property differentiation; poverty; crisis of industrialism